Comparison of Different Methods of Non-contact Vibration Measurement. (2017) - Lezhin, D.S.; Falaleev, S.V.; Safin, A.I.; Ulanov, A.M.; Vergnano, D.
Abstract: Practical problems of vibration measurement and calculation are considered. Different non-contacts methods of vibration measurement (with Polytec® OFV-534 1D laser vibrometer, Polytec® PSV-400-3D scanning vibrometer, ARAMIS® system) and a comparisons between each other and with Finite Element Method modeling (by ANSYS® software) are presented. The experiment is fulfilled for high pressure shaft of NK-8 gas turbine engine. Difference of middle value for first resonance frequency obtained by three different ways is less than 0.2% only. Difference of second resonance frequency is less than 0.4%. It means it is possible to use 1D laser vibrometer for measurement of vibration of detail for limited access directly in engine structure, which is more correct. ARAMIS® gives a limited but precise picture of deformed shape and simultaneous displacement of all surface points of researched object in the researched place. It allows applying of boundary condition for software calculation more correctly.